Deep eutectic solvent liquid phase microextraction, powered by ultrasonic system, for determination of ?-carotene in food samples - Kizil, Nebiye; Beydagi, Buse Bozan; Yola, Mehmet Lutfi; Soylak, Mustafa; Kızıl, Nebiye; Yola, Mehmet Lütfi (Academıc Press Inc Elsevıer Scıence)
The research work is mainly concerned with the extraction of beta-carotene, which is a terpenoid compound, from food and fruit samples using deep eutectic solvent based liquid phase extraction. Deep eutectic solvent liquid phase microextraction method, powered by ultrasonic mixing, (DES-UP-LPME) was carried out with deep eutectic solvent (DES) consisting of tetrabutylammoniumbromide (TBAB) and decanoic acid (DA). Key parameters such as pH, sample volume, tetrahydrofuran (THF) volume, DES type and volume, matrix effect, ultra-sonication/centrifugation time were optimized to increase the extraction efficiency of beta-carotene. Quantitative recoveries were obtained when pH, TBAB:DA ratio and sample volume were 3, 1:3 and 30, respectively. The limit of detection (LOD) and limit of quantification (LOQ) were found to be 0.005 mu g/mL and 0.015 mu g/mL, respectively. Various food samples were analyzed spectrophotometrically by using the developed DES-UP-LPME at 450 nm. The addition/recovery studies were also performed on water samples to evaluate the accuracy of the method.
Keywords: Deep eutectic solvent; beta-Carotene; Bioactive compounds; UV-vis spectrophotometry; Tetrabutylammoniumbromide (TBAB); Decanoic acid (DA); Preconcentration